Replacement and substitution:
However, equivalences allow us to change one sentence with another without affecting the meaning, it means we know already that replacing one side of an equivalence into the other will have no effect so whatever on the semantics: but it will still be true for the same models. Just assume there we have a sentence S with a sub expression A that we write like S[A]. But there if we know A≡B so we can be sure the semantics of S is unaffected because we replace A with B, i.e. S[A] ≡S[B].
However, there we can also use A ≡B to replace any sub expression of S that is an instance of A. But there point to be remember that an instance of a propositional expression A is a 'copy' of A when some of the propositions of have been consistently replaced by original sub expressions, e.g. to every P has been replaced by ¬Q. So than we call this replacement a substitution, and a mapping from propositions to expressions. Through applying a substitution U to a sentence S, we find a new sentence S.U that is an instance of S. There always Ii is easy to show that if there A ≡B so A.U ≡B.U just for any substitution U, that is. an instance of an equivalence is as well an equivalence. Thus, an equivalence A ≡B allows us to change a sentence S[A'] to a logically and fundamentally equivalent one S[B'] but if we have substitution U like that A' = A.U and B' = B.U.